2010
DOI: 10.1007/s10725-010-9458-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of chitinase and stilbene synthase genes in Florida hybrid bunch grapes to Elsinoë ampelina infection

Abstract: Florida hybrid bunch grape (Vitis spp.) cultivars with commercial value are susceptible to anthracnose disease caused by the fungi, Elsinoe¨ampelina. The Florida grape industry is keen on improving anthracnose tolerance characteristics of these grape cultivars as the cultivation of European grapes is limited in Southeastern United States due to Pierce's disease incidence. In this connection, a molecular approach was taken to identify and characterize the gene/s differentially expressed upon infestation with E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Vasanthaiah et al . demonstrated that chitinase and stilbene synthase genes were more rapidly expressed in tolerant cultivars after inoculation with an anthracnose pathogen [ 27 ]. In addition to PAL and CHS, other enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vasanthaiah et al . demonstrated that chitinase and stilbene synthase genes were more rapidly expressed in tolerant cultivars after inoculation with an anthracnose pathogen [ 27 ]. In addition to PAL and CHS, other enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The chitinase was up-regulated in resistant plant of wheat, rice, grape and Acacia coa (Mohammadi et al, 2002;Shrestha et al, 2008;Vasanthaiah et al, 2010;Rushanaedy et al, 2012) but there was no increase in the susceptible plant. Shrestha et al (2008) and Orlowska et al (2012) showed that chitinase gene was induced in both resistant and susceptible plant but was induced at earlier time point in resistant compared to susceptible plant.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing and characterization of these genes revealed their similarity with chitinase III, PR 4 and 10, chalcone synthase, and stilbene synthase. Further, realtime PCR analysis revealed that the expression patterns of gene-encoding enzymes, such as chitinase and stilbene synthase, were higher than that of other genes during E. ampelina infestation [94]. These genes are known to play an important role in plant defense against fungal pathogens.…”
Section: Anthracnosementioning
confidence: 99%